THE INFLUENCED FACTORS OF SPIRITUAL WELL-BEING: A SYSTEMATIC REVIEW - Hayatul Khairul Rahmat; A. Said Hasan Basri; Rezki Masda Putra; M Mulkiyan; Sri Wanda Wahyuni; C Casmini (Sociocouns: Journal of Islamic Guidance and Counseling, 2022)
Well-being in essence is not just material or physical prosperity, but how each individual gets the opportunity to develop his full potential, including spirituality. This study aims to explore the factors that influence spiritual well-being. The method used in this research is a systematic review. The findings of this study are factors that affect spiritual well-being including: mental health, spiritual coping, life satisfaction, hope, primary emotions, mindfulness, self-compassion, perceived social support, quality of life, adjustment to chronic diseases, psychological disorders, psychological well-being, and psychological resilience.